Newsletter
042-0024-001 SPANISH MEDICAL AID COMMITTEE REFUGEES IN ENGLAND. The Committee has undertaken, in agreement with the British Committee for Refugees from Spain, the medical care of all the refugees in this country. We have organized a panel of doctors and nurses who give their professional services free, and also arrange for hospital and dental treatment for refugee patients. REFUGEES IN THE FRENCH CAMPS. We have contributed £900. to the Centrale Sanitaire Internationale, to be spent on medicaments, soap, clothing and disinfectants for the refugees in the camps. Furthermore, special milk foods for typhoid cases, microscopes and X-Ray materials have been sent direct to the camps, and parcels labelled from "England" have been sent direct to refugees. As a result of the efforts of the French and British peoples the conditions in the camps have improved enormously, (see the "News Chronicle", July 11th, 1939), but the plight of these unfortunate thousands, homeless, separated from wives, husbands, children and friends, is only equalled by the lot of the thousands of refugees from Hitler's Greater Germany. REFUGEE SHIPS. We supplied all the medicaments for the first Refugee Ship, the " Sinaia ", which left Port Vendres on the 24th May last and arrived in Vera Cruz on June 13th. The arrangements were made with the C.S.I. in Paris and in two days, by keeping the factories working night and day, the large quantities of medical stores required for 1800 refugees were packed and sent to the " Sinaia ". In addition, the fifteen Spanish doctors who were emigrating to Mexico were each supplied with a case of instruments and the equipment needed to start life afresh in the country of their adoption. We are proposing to accept full responsibility for the payment of the fares to Mexico of another group of about twenty Spanish doctors and nurses, including their equipment. MADGE ADDY BACK FROM UCLES. Nurse Madge Addy, who was a member of the British Medical Unit in Spain from the beginning of March 1938, stayed on in Ucles, the evacuation hospital on the Madrid front, until the bitter end. After extreme hardships and perils, she succeeded in returning to England on June 30th last, via San Sebastian and Hendaye - and that only after the Spanish Medical Aid Committee had intervened with the British Foreign Office to secure her a visa. ANGLO-IBERIAN SOCIETY. Wilfrid Roberts, M.P. has issued an appeal, sponsored by a group of prominent scientists, writers and artists, for support for a proposed Anglo-Iberian Centre. It is intended to establish a (strictly non-political) Club, at which Spanish refugees will have an opportunity of meeting British men and women interested in Spanish culture and at which lectures, concerts, dances and other functions will be organised. Those interested are requested to apply for further details to George Jeger, Hon. Secretary, Anglo-Iberian Society, 69, Great Russell Street, W.C.1. 292/946/42/24